PENERAPAN METODE DISCOVERY LEARNING PADA PEMBELAJARAN MENULIS TEKS EKSPOSISI - Urhalinah Kania Dewi; Puja Srinapiana Silva; Wikanengsih Wikanengsih (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2018)
This research is based on the problem of writing writing that occurs in high school, especially in writing exposition texts. The purpose of this study to improve the results of the students' degrees in writing exposition texts and to know the results before and after using discovery learning method. The method used in this research is experiment. The sample of research is the students of class X IPS 1 in the experimental class and the students of class X IPS 2 in the control class. The results showed that there were significant differences between before and after using discovery learning method. Based on the data obtained by researchers there is a difference from the initial test and the final test with an average of 48.7 preliminary tests and the final test of 79.0. Judging from the results of the average student who increased can be concluded that the use of discovery learning method suitable or use in writing text writing exposition.